Diversity and Distribution of Forest Insects - Gwiazdowicz, Dariusz J. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Forests are the richest and most complex ecosystems in the world. Due to the abundance of species and their intricate relationships, huge problems are faced when investigating and analyzing them, despite the fact that increasingly sophisticated research tools are currently available. This is also true in the case of the largest group of animals in the world, i.e., insects inhabiting the forest environment. We are currently living in times of dramatic environmental changes triggered by human activity. The effects of climate change are evident and lead to changes in forests. Growing numbers of insect species are being threatened, and it is our responsibility to protect them. This Special Issue of our journal aims to provide a platform for scientific discussions on an array of research problems, such as geographic or historic diversity of forest insects, their variability, habitat preferences, as well as their monitoring or use as bioindicators of environmental changes. We are convinced that this Special Issue will not only be a source of inspiration for further research but will also contribute to reaching a reasonable compromise between the necessary protection of forests and the need for economic benefits. It is our belief that entomological studies will be of considerable value in these efforts.